TEKNOLOGI INFORMASl DAN KOMUNIKASI (TIK) LEVERAGE MENUJU REFORMASI BIROKRASI JCT LEVERAGE TOWARDS BUREAUCRACY REFORMATION - Adi, Suroto (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
The progress of information and communication technology (ICT) has created the opportunity to support the basic principal organizational changes within the government, especially in the area of business processes and public services which now call as bureaucracy reform. Formerly, information and communication technology dedicated to support decision making and policy formulation, now may have closed relationship with effectiveness and efficiency of government business processes and public services as well. Today, the ideal concept of bureaucracy that presented by Max Weber are still followed by many organizations. Unfortunately, it makes inflexible bureaucracy and therefore the objective of national development was unsuccessful. It happened due to ineffective and inefficient of business processes as well as business events. Because of government environment changes and the progress and utilization oflCT in real world, there are two concepts, namely "good governance" and "reinventing government" give direction to implement to bureaucracy reform in which ICT takes role significantly and leverages bureaucracy reform. This paper aim to identify the important aspects related with bureaucracy reform and which area ICT will contribute to support bureaucracy practices. A review of some relevant I iteraturesÂ·and assessment of several cases of government business processes and public services in Indonesia are presented. Some preliminary results are reported future research needs are discussed. There are several importance ofICTs positive impacts to bureaucracy reform then become "leverage", such as the improvement of government business processes, serve timely and precisely for accountable decision making, and improved public services as well. Bureaucracy reform in Indonesia tend to follow "good governance concept" and ICT demonstrates as leverage.